The Impact of Father's Support and Mother's Psychology on the Responsiveness of Mother Towards Child under Two Years of Age - Riana Lestari, Tri (KnE Life Sciences, 2019)
Mothers with a higher responsiveness to their children show a higher development level for their children. This study aimed to find a correlation between a father's support and the mother's psychological impact on the mother’s responsiveness in raising up their children. This research used a cross-sectional study on mothers with children aged 3 months to 2 years. The examined variables were: mother's psychological factors, father's support, and the responsiveness of the mother. This research sample used a Multistage Random Sampling technique in 3 districts and 20 villages in Blitar. The study involved 279 mothers as the research sample. This study used a responsiveness questionnaire instrument and an observation sheet, which was adopted from the Home Observation for Measurement of the Environment (HOME) Inventory. Inferential data were analyzed by PLS (Partial Least Square) version 2.0. According to the finding, there are two primary factors that affect the responsiveness of mothers – the psychological factors of mother and father. Further research could clarify and quantify the consistency of the variables found in this model, so a new model for enhancing the mother's responsiveness could be found.